(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This article is dedicated to investigating the technology of developing design thinking through art pedagogy. Design thinking is viewed as an innovative approach that aids in fostering students’ creative and systematic thinking. Art pedagogy is a methodology for organizing the educational process through the medium of art. This study explores the potential for developing students’ creative and analytical skills through the integration of design thinking and art pedagogy. The article provides insights into effective methods for cultivating students’ creative thinking and problem-solving abilities. The research findings highlight the significance of implementing new technologies in art and design education.